Efektivitas Pelaksanaan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan dalam Menekan Tingkat Kecelakaan Lalu Lintas - Risti Dwi Ramasari (KEADILAN PROGRESIF, 2015)
Amendment Act Traffic and Road Transportation can be a momentum for the Traffic Police for further streamline further the accident rate, but that with greater penalties for violation of traffic is expected to reduce the level of traffic violations. The problem in this research is how the effectiveness of the implementation of Law No. 22 Year 2009 regarding Traffic and Road Transportation in reducing traffic accidents. The method used in this thesis research is juridical no¬rmatif and empirical juridical approach. The effectiveness of the implementation of Law No. 22 Year 2009 regarding Traffic and Road Transportation in reducing traffic accidents was already effective, where the accident rate after it is passed and the enactment of Law No. 22 Year 2009 regarding Traffic and Road Transportation has decreased, so also with the level of evidence of the offense (Tilang). Factors that hamper the implementation of Law No. 22 Year 2009 regarding Traffic and Road Transportation in reducing traffic accidents, among others, include: lack of personnel; facilities and infrastructure; Low professional level members; operational funds; and low public awareness. The causes of road accidents by drivers of public transport can arise due to external factors and internal. External factors such as lack of knowing the terrain and signs and traffic regulations, while the internal factors include a driver's ability is lacking, be it  due to fatigue, drowsiness and can also be due to the driver's knowledge and skills that are less good.